2017
DOI: 10.1155/2017/6949835
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Ethnopharmacological Applications, Pharmacological Activities, and Bioactive Compounds of Mangifera indica (Mango)

Abstract: Mangifera indica (family Anacardiaceae), commonly known as mango, is a pharmacologically, ethnomedically, and phytochemically diverse plant. Various parts of M. indica tree have been used in traditional medicine for the treatment of different ailments, and a number of bioactive phytochemical constituents of M. indica have been reported, namely, polyphenols, terpenes, sterols, carotenoids, vitamins, and amino acids, and so forth. Several studies have proven the pharmacological potential of different parts of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
125
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(129 citation statements)
references
References 230 publications
(204 reference statements)
1
125
0
3
Order By: Relevance
“…It is estimated that there are about 1000 mango varieties with various names grown all over the world. India is known to be the highest mango cultivating country [6]. M. indica has been an important herb in the Ayurvedic and indigenous medical systems for over 4000 years.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that there are about 1000 mango varieties with various names grown all over the world. India is known to be the highest mango cultivating country [6]. M. indica has been an important herb in the Ayurvedic and indigenous medical systems for over 4000 years.…”
Section: Introductionmentioning
confidence: 99%
“…These infections generate purulent material forming abscesses and can cause minor infections of the skin and soft tissues and invasive infections such as: infections of the central nervous system, respiratory, gastrointestinal and urinary tract, bacteraemia and osteomyelitis. [16][17][18][19][20] In the present investigation the antibacterial activity of different mango leaf extracts on S. aureus strain ATCC 6538 was evaluated, the ethanolic and hydroalcoholic extracts were used at 50% and 100% dilutions on bacterial cultures, using the diffusion method from Kirby-Bauer wells and it was found that in effect the four dilutions have extremely sensitive activity, there are significant differences between them and in comparison with the positive control (chlorhexidine 0.12%). The results obtained in this research agree with similar studies carried out by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…Mangifera indica has been reportedly used as water coagulant in traditional water purification system. In addition to the well-documented antimicrobial activities of M. indica (Oluduro et al 2010;Singh et al 2010), it also possessed numerous health benefits including anti-ulcer, antidiarrhoea, diuretic, anti-hypertensive, anti-cancer activities and antiparasitic activities (Meran et al 2017). Thus, as a solution to the aforementioned, M. indica could serve an alternative natural coagulant to replace synthetic aluminum thus increasing the safety and suitability of water for human consumption.…”
Section: Introductionmentioning
confidence: 99%